THE EFFECT OF EXTRINSIC MOTIVATION AND JOB STRESS ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT. BANK NEGARA INDONESIA (PERSERO) TBK. USU BRANCH MEDAN - Holong Melisa Sari Pasaribu; Ritha F Dalimunthe; Beby Karina F. Sembiring (CV. Radja Publika, 2023)
The success of employees in an organization, especially in banking, has a big impact on how well the resources can meet customer needs and satisfaction, which is the goal of a business. Customer satisfaction is a big part of the company's goals, which has a lot to do with how the company manages its human resources. As a result, every employee should be required to improve their performance and work towards those goals at all times. On the other hand, job stress and things that motivate employees outside of work also affect how satisfied they are at work. This study aims to analyze the effect of extrinsic motivation and job stress on employee performance with job satisfaction as an intervening variable at PT Bank Negara Indonesia, Tbk USU Branch. This research was conducted using a quantitative approach, and data were collected through questionnaires distributed to 93 bank employees by conducting Z-sobel testing on the intervening test. The results showed a positive direct influence between extrinsic motivation and employee performance. Extrinsic motivation is proven to encourage increased employee performance. Furthermore, this study also found a negative direct effect between job stress and employee performance. High levels of work stress can hinder employee performance, reduce productivity, and affect overall work quality.